REGULASI DIRI ORANG TUA DALAM PENGASUHAN ANAK AUTISM SPECTRUM DISORDER DI MASA PANDEMI - Rini Budi Setyowati; Weny Savitry Sembiring Pandia (Provitae: Jurnal Psikologi Pendidikan, 2023)
Parenting of Autism Spectrum Disorder children has great challenges especially during the covid-19 pandemic due to reduced social support, increased parental duties, and the child behavior. Parental self-regulation is important because it affects positive parenting practices, which support the optimization of children's development. This study aims to understand the description of parental self-regulation in parents of Autism Spectrum Disorder children during the covid-19 pandemic. This research is descriptive explanatory design-mixed methods, included 120 parents of children with Autism Spectrum Disorder completed the “Me as a Parent” questionnaire, measured four parental self-regulation domains: self-efficacy, personal agency, self-management and self-sufficiency. Interviews are conducted on representatives of high, moderate, and low categories of participants to obtain qualitative data. The result shows that most of the participants have moderate category of parental self- regulation, approximately a quarter of the participants in the high category, and a small proportion in the low category. Descriptive data analysis showed that some of the participants had low parental self-regulation, which was supported by qualitative data. Based on the results, a training was designed that aims to improve parental self-regulation of parents with Autism Spectrum Disorder children, through developing domains with discussion and practice.